2020
DOI: 10.15549/jeecar.v7i3.477
|View full text |Cite
|
Sign up to set email alerts
|

The role of Exchange Rates in non-oil export activity: evidence from Azerbaijan

Abstract: The dependence of the Azerbaijani economy on oil makes urgent the issue of diversifying the economy to increase its competitiveness.  This, in turn, necessitates the formation of techniques to qualitatively assess the effectiveness of diversification to alternative, namely non-oil exports. This study aims to develop an econometric model to assess the impact of non-oil export diversification on Azerbaijan's economic development. Based on the literature analysis and using hierarchy analysis by T. Saaty, a list o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Many scientific studies have shown that increasing trade openness, combined with increased participation in global value chains, can improve export diversification and attract foreign investment, and can provide a 5-10% annual increase in a country's income (Ganbarov, Alieva & Babazade, 2020). However, one of the severe obstacles to achieving the set tasks by Azerbaijan is the presence of numerous differences and incompatibility in the maintenance of financial statements of companies compiled in different countries, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Many scientific studies have shown that increasing trade openness, combined with increased participation in global value chains, can improve export diversification and attract foreign investment, and can provide a 5-10% annual increase in a country's income (Ganbarov, Alieva & Babazade, 2020). However, one of the severe obstacles to achieving the set tasks by Azerbaijan is the presence of numerous differences and incompatibility in the maintenance of financial statements of companies compiled in different countries, e.g.…”
Section: Introductionmentioning
confidence: 99%